Endogenous Growth, Skill Obsolescence, and Output Hysteresis in a New Keynesian Model with Unemployment - WOLFGANG LECHTHALER; MEWAEL F. TESFASELASSIE (Journal of Money, Credit and Banking, 2022)
We embed skill obsolescence and endogenous growth into a New Keynesian model with search-and-matching frictions. The model accounts for key features of the Great Recession: the “productivity puzzle” and the “missing disinflation puzzle.” Lower aggregate demand raises long-term unemployment and the training costs associated with skill obsolescence. Lower aggregate employment hinders learning-by-doing, which slows down human capital accumulation, feeding back into even fewer vacancies than justified by the demand shock alone. These feedback channels mitigate the disinflationary effect of the demand shock while amplifying its contractionary effect on output. The temporary growth slowdown translates into output~hysteresis.
Keywords: 330; endogenous growth; search and matching; unemployment; monetary policy; output hysteresis